Citizenship In Immigration Perspective - Yogi Prabowo; Taufiqurrohman Syahuri (Polteknik Imigrasi, 2022)
Citizenship shows the relationship between the state and citizens. The right to citizenship is the basic right of every person. However, the state absolutely can determine the principles in determining citizenship. Indonesia has made arrangements for citizenship through Law Number 12 of 2006 regarding Citizenship of the Republic of Indonesia. This research uses normative legal analysis because the object of this research is the legislation which has permanent and binding legal force. Conceptually, Indonesia makes Pancasila as its own views, ideas, and ideals about ideal citizenship. In determining citizenship status, Indonesia adheres to the ius sanguinis principle and the ius soli principle to a limited extent. Basically, Indonesia applies single citizenship, but children can be given limited dual citizenship for the sake of fulfilling human rights and protection. With the regulation of citizenship both in national and international law, in fact there are still stateless people. Indonesia is also inseparable from the existence of stateless people. In line with the regulation of citizenship in Indonesia, Immigration is here to provide services and protection to the status of Indonesian citizenship, as well as to ensure the existence and activities of foreign nationals in the territory of Indonesia in order to guarantee the potential, dignity and worth of every person in accordance with human rights based on Pancasila and The 1945 Constitution of the Republic of Indonesia.